The interrelation of hydrodynamic forces and swimming speed in breaststroke - Ungerechts, B. E. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
In swimming the hydrodynamic forces of arms and legs in motion propel the swimmer resulting in a certain swimming speed. This paper examines whether the intracyclic velocity of a swimmer's body can be explained by a 3-dimensional kinematic analysis of the movements of the hands - based on the present knowledge in biomechanics of swimming. Calculating both the fluid forces of the hands in motion and the forces necessary to reach a certain swimming speed (thrust forces) respectively, the degree of coincidence of both forces can be checked. Ninety-nine pairs of forces, calculated for the propulsive part of the armstroke of eight breaststrokers, were compared statistically. The results reveal that 80% of all pairs of forces were statistically equal, indicating close covariation. Moreover, the comparison of the absolute values of the different force terms demonstrated that the fluid forces produced by the hands account for only about half of the entire thrust forces. This in turn requires the consideration of the fluid forces provided by the arms which account for the second half. It is concluded that the biomechanical approach chosen here, supplemented with some adjustments, might be a valuable method for diagnosis and prognosis of elite swimmers' technique and efficiency.